Physical Behavior of a.PP/LDPE Blends under Different Conditions (Journal of University of Babylon for Engineering Sciences, 2019)
The aim of this work was to make LDPE /a.PP blends for  economically attractive by (10/90, 20:80, 30:70, &50:50 w/w) ratios via injection molding carried out under 180 o C injection temperatures and to evaluate their mechanical properties including :( Density, Tensile Strength, Elongate to Break, Impact  Strength, Bending Modulus,&  Young's  Modulus . we notice that the blend behavior dependent on its composition, and injection temperature .Results show there are an increasing of impact strength and bending modulus with increasing of (LDPE) contain and the highest value of these properties were at (50:50) weight ratio, while it has the highest Young's modulus at (30:70) wt%. 180 o C as injection temperature leads to translate the mechanical behavior from ductile to stiff behavior. DSC curves show that the blends is immiscibility , also thermal degradation was decreased with increasing of LDPE to (50%).Also the Melt flow index decreased from (5.04)-(4.01) (g/10 min) with increasing of LDPE from (30%) to (50%).